Judicial Reform Of Kazakhs At The End Of Xix Century - Saken Utaliev, Marat Islamov; Aman, Alibek; Naimanbayev, Bekmurat; Abdirahmanov, Tolobek (Opción, 2019)
The aim of the study is to investigate the judicial reform of Kazakhs at the end of XIX century via the science-based methods used in all humanities (dialectical, systemic) and historical methods of research (retrospective, comparative and contrastive). As a result, at a boundary of the XIX-XX centuries, the position of Islam ignoring by the Russian authorities actually turned into hostile. In conclusion, it is important to note the discriminatory nature of the legislation of the Russian Empire concerning various ethnic groups inhabiting the region and a privileged position of separate estates.